Breast cancer in pre-menopausal women in West Africa: analysis of temporal trends and evaluation of risk factors associated with reproductive life - (:unkn) unknown (My University, 2013)
Sighoko, Dominique Kamate, Bakarou Traore, Cheick Malle, Brahima Coulibaly, Bourama Karidiatou, Agnes Diallo, Coulibaly Bah, Ebrima McCormack, Valerie Muwonge, Richard Bourgeois, Denis Gormally, Emmanuelle Curado, Maria Paula Bayo, Sine Hainaut, Pierre eng Research Support, Non-U.S. Gov't Netherlands Edinburgh, Scotland 2013/03/16 06:00 Breast. 2013 Oct;22(5):828-35. doi: 10.1016/j.breast.2013.02.011. Epub 2013 Mar 13.
Keywords: African Research